Awareness and impact of the 'Bubblewrap' advertising campaign among Aboriginal smokers in Western Australia - Boyle, T.; Shepherd, Carrington; Pearson, G.; Monteiro, H.; McAullay, D.; Economo, K.; Stewart, S. (BMJ Publishing Group, 2010)
Background Antismoking mass media campaigns have been shown to reduce smoking prevalence in the mainstream community, however there is little published research on their effect on Aboriginal Australian smokers. Objectives To evaluate the awareness and impact of a mainstream mass media advertising campaign (the ‘Bubblewrap’ campaign) on Aboriginal smokers in the state of Western Australia. Methods A personal intercept survey was conducted in July 2008 across three sites (the Perth metropolitan area and the non-metropolitan towns of Kalgoorlie and Broome). An opportunity or convenience sampling strategy was used to recruit Aboriginal participants, and face-to-face interviews were conducted with 198 Aboriginal smokers to ascertain awareness of the campaign advertisements, whether they were seen as believable and relevant, and the impact the advertisements had on smoking behaviour.Results The majority of the participants interviewed had seen and/or heard the ‘Bubblewrap’ campaign advertisements, although there was considerably greater awareness of the television advertisement than the radio advertisements. Both forms of advertising were considered to be believable and relevant by the majority of Aboriginal smokers. Most of the smokers interviewed thought about cutting down and/or quitting after seeing or hearing the advertisements. Conclusions Our findings suggest that mainstream antismoking mass media campaigns can positively influence the thoughts and behaviours that Aboriginal smokers have, and exhibit, towards quitting smoking. Notwithstanding this, advertisers should continue to look for better ways to incorporate Aboriginal themes in campaign messages. Future mainstream antismoking campaigns should source sufficient funds to ensure that advertising messages reach the large Aboriginal populations in regional and remote Australia.